Magnetoreception in Microorganisms. Issue 4 (April 2020) - Monteil, Caroline L.; Lefevre, Christopher T.
Abstract : Magnetoreception is the sense whereby organisms geolocate and navigate in response to the Earth's magnetic field lines. For decades, magnetotactic bacteria have been the only known magnetoreceptive microorganisms. The magnetotactic behaviour of these aquatic prokaryotes is due to the biomineralization of magnetic crystals. While an old report alleged the existence of microbial algae with similar behaviour, recent discoveries have demonstrated the existence of unicellular eukaryotes able to sense the geomagnetic field, and have revealed different mechanisms and strategies involved in such a sensing. Some ciliates can be magnetically guided after predation of magnetotactic bacteria, while some flagellates acquired this sense through symbiosis with magnetic bacteria. A report has even suggested that some magnetotactic protists could biomineralize magnetic crystals. Highlights: Magnetoreception is a sense whereby aquatic microorganisms detect the Earth's magnetic field lines to geolocate. Bacterial magnetoreception is due to the biomineralization of nano-sized magnets within organelles called magnetosomes. Some microbial eukaryotes may become transitorily magnetoreceptive by preying on magnetotactic bacteria. Other unicellular flagellates evolved this sense sustainably by establishing a symbiosis with magnetic bacteria. A recent report suggests that some magnetoreceptive microeukaryotes can form their own magnetosome-like chains.